Deliberate play, deliberate practice and deliberate preparation - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
A common assumption in sport is that to achieve timely success individuals` training must start early so that they `get the required time in`, as dictated by the now ubiquitously cited 10,000-hours rule. This `rule` is widely criticised and as a result a Deliberate Play model has gained traction. This chapter presents the pitfalls of solely applying either model; we argue that the extant models do not account for the focused instruction and structured practice required to develop and refine physical and psychological skills and a framework for acquiring the essential base of general movement ability is absent. The chapter then provides an overview of a more appropriate and effective approach to both participation and performance, `Deliberate Preparation` that provides a robust foundation of psychomotor and psycho-behavioural skills. The importance of this unified and structured approach is outlined, and the roadblocks and facilitators of providing practical implementation are discussed so that readers can evaluate the quality of early provision in their environment.